Contribution to the research of pathological phenomena in Republic Srpska - Šiljak, Milica (Sociološki pregled, 2020)
The article “Deviant behaviour in Republic Srpska” by Biljana Milošević Šošo, represents a scientific contribution to the study of sociopathological phenomena with special reference to the societies in the transition process. The monograph is a synthesis of the most important theoretical approaches in sociological pathology and empirical indicators of the most common forms of deviant behaviour in Republic Srpska. The author expresses her critical attitude towards the existing social-value system, which is a determinant for the emergence and development of specific forms of sociopathological behaviour in the society in Republic Srpska.